Konseling Religius Dalam Mengatasi Kesehatan Mental Pasca Pandemi Covid 19 - M. Fahli Zatrahadi; Herman Nirwana; Mudjiran Mudjiran; Yeni Karneli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Religious counseling in dealing with mental health after the COVID-19 pandemic. I conducted this research using the library method used in this study using a qualitative approach (library research). Literature-based as study material is the object of research. The analytical technique used in answering the research problem is using content analysis techniques and strengthened by using the results of the Nvivo software coding. The results show that the spread of the COVID-19 virus impacts people’s mental health disorders. So that in reality it requires counseling help to reduce anxieties because of the news that the number of deaths has increased because of corona. Here, religious counseling can be carried out by bathing repentance, repentance prayers, remembrance, and other worship. Likewise, in dealing with the post-covid-19 pandemic so that past events do not happen again and always remember Allah SWT.